2017
DOI: 10.1039/c7cp02519j
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical self-assembly of photoluminescent CdS nanoparticles into a bile acid derived organogel: morphological and photophysical properties

Abstract: We have described a strategy towards integrating photoluminescent semiconductor nanoparticles into a bio-surfactant derived organogel. A facially amphiphilic bile thiol was used for capping CdS nanoparticles (NPs) which were embedded in a bile acid derived new organogelator in order to furnish a soft hybrid material. The presence of CdS NPs in a well-ordered 1D array on the organogel network was confirmed using microscopic techniques. Photophysical studies of the gel-NP hybrid revealed resolved excitation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…BS and BSD in the form of gels, solutions, or mixtures with conventional surfactants can be used to template the in situ formation or organization of different types of inorganic nanostructures such as silica, metal, , and semiconductive nanoparticles, , nanoGUMBOS, , and semiconductive nanotubes (Figure a). , Solutions of BSs can be also used in metallic nanoparticle synthesis, where it was observed that BSs present the unusual double role of capping and reducing agents at room temperature. Different examples of BS- and BSD-capped spherical nanoparticles are reported along with other unconventional morphologies such as hexagonal and triangular plates .…”
Section: Applicationsmentioning
confidence: 99%
“…BS and BSD in the form of gels, solutions, or mixtures with conventional surfactants can be used to template the in situ formation or organization of different types of inorganic nanostructures such as silica, metal, , and semiconductive nanoparticles, , nanoGUMBOS, , and semiconductive nanotubes (Figure a). , Solutions of BSs can be also used in metallic nanoparticle synthesis, where it was observed that BSs present the unusual double role of capping and reducing agents at room temperature. Different examples of BS- and BSD-capped spherical nanoparticles are reported along with other unconventional morphologies such as hexagonal and triangular plates .…”
Section: Applicationsmentioning
confidence: 99%
“…A lithocholic acid‐derived dimeric amide was synthesized and used as a gelator in organic solvents. [ 73 ] Photoluminescent CdS QDs were synthesized in the gel matrix and formed 1D arrays due to their interactions with the gelator molecules. [ 73 ] Bhowmik et al [ 74 ] developed a strategy for the fabrication of LnF 3 NPs using Ln cholate hydrogel.…”
Section: Fabrication Of Composite Gelsmentioning
confidence: 99%
“…[ 73 ] Photoluminescent CdS QDs were synthesized in the gel matrix and formed 1D arrays due to their interactions with the gelator molecules. [ 73 ] Bhowmik et al [ 74 ] developed a strategy for the fabrication of LnF 3 NPs using Ln cholate hydrogel. This technique offers the advantages of simple room‐temperature synthesis without the use of capping agents.…”
Section: Fabrication Of Composite Gelsmentioning
confidence: 99%
“…Further attempts of bile acids functionalization have been presented in recent reports. There are a couple of reports discussing p -tertbutylbenzoyl derivatives of cholic acid, which when mixed with a copolymer and in a covalent conjugation with tripeptide demonstrate fabrication of thermoresponsive supramolecular structures [ 91 ] and twisted nanoribbons [ 92 ] as well as dimeric bile acid derivatives acting as organogelators for the design of hybrid nanomaterials [ 93 ].…”
Section: Self-assembly Of Amphiphilic Compoundsmentioning
confidence: 99%